The Role of Allosteric Coupling on Thermal Activation of Thermo-TRP Channels - Jara-Oseguera, Andrés (The Biophysical Society, 2013)
Thermo-transient receptor potential channels display outstanding temperature sensitivity and can be directly gated by low or high temperature, giving rise to cold- and heat-activated currents. These constitute the molecular basis for the detection of changes in ambient temperature by sensory neurons in animals. The mechanism that underlies the temperature sensitivity in thermo-transient receptor potential channels remains unknown, but has been associated with large changes in standard-state enthalpy (ΔH(o)) and entropy (ΔS(o)) upon channel gating. The magnitude, sign, and temperature dependence of ΔH(o) and ΔS(o), the last given by an associated change in heat capacity (ΔC(p)), can determine a channel’s temperature sensitivity and whether it is activated by cooling, heating, or both, if ΔC(p) makes an important contribution. We show that in the presence of allosteric gating, other parameters, besides ΔH(o) and ΔS(o), including the gating equilibrium constant, the strength- and temperature dependence of the coupling between gating and the temperature-sensitive transitions, as well as the ΔH(o)/ΔS(o) ratio associated with them, can also determine a channel’s temperature-dependent activity, and even give rise to channels that respond to both cooling and heating in a ΔC(p)-independent manner.